Tissue-specific expression of the 79B actin gene during Drosophila development. - Courchesne-Smith, C.L.; Tobin, S.L. (Developmental Biology, 1989)
We report temporal and tissue-specific patterns of expression of the 79B actin gene in Drosophila. The pattern of accumulation of 79B actin transcripts was determined and compared to the expression of a 79B actin promoter fused to the Escherichia coli beta-galactosidase reporter gene. This chimeric gene contained approximately 4 kb of 5' flanking DNA from the 79B actin gene. We found that beta-galactosidase activity in transformants was localized in the same tissues and possessed the same developmental timing as the transcripts of the 79B actin gene. Expression is limited to tubular-type muscles found predominantly in the thorax and leg, including the direct flight muscles, pleurosternal muscles, and muscles of the various leg segments. In addition, the 79B actin gene is expressed in muscles which support the head and abdomen, in the scutellar pulsatile organ, and in abdominal muscles which are present only in male flies.